M41. TRAJECTORIES AND PREDICTORS OF OUTCOME IN SCHIZOPHRENIA: THE BENEFICIAL ROLE OF AMISULPRIDE. (18th May 2020) - Drosos, Petros; Johnsen, Erik; Bartz-Johannessen, Christoffer A; Kroken, Rune A
Abstract: Background: Schizophrenia is a serious illness and treatment with antipsychotic drugs remains one of the most effective types of treatment. The course of schizophrenia, however, is highly heterogeneous and currently it is not possible to predict which patient will respond adequately to which antipsychotic drug. The aim of our study was to define trajectories regarding response to antipsychotic drug treatment in patients with schizophrenia spectrum disorders. A second aim was to evaluate demographic factors and antipsychotic drugs as predictors for the different trajectories. Methods: Best Intro is a randomized, rater-blind, head-to-head comparison of amisulpride, aripiprazole and olanzapine. Adult patients with a diagnosis in the schizophrenia spectrum (ICD-10 diagnoses F20-29) were included. Participants had symptoms of ongoing psychosis as determined by a score of four or more on at least one of the following PANSS (Positive and Negative Syndrome Scale) items: P1 (delusions), P3 (hallucinations), P5 (grandiosity), P6 (suspiciousness/persecution) or G9 (unusual thought content). Patients were followed over a period of 52 weeks and the assessment points were at baseline, after one week, three weeks, six weeks, three months, six months, nine months, and 12 months. Totally 359 patients were assessed for eligibility, and 144 of them were enrolled and randomized to one of the study drugs. We used the R statistical program to define trajectories of antipsychotic response. Results: We identified three different trajectories regarding the reduction of PANSS total score, with Bayesian information criterion (BIC) = 6157 (BIC for two groups=6164 and for four groups=6171). A large group of patients (N=106, 74%) showed a trajectory of good improvement in PANSS total score over the first 26 weeks of follow-up and maintained it after one year with a total of 35% reduction in PANSS total score (Good response group). A second group of patients (N=19, 13%) followed a trajectory of quick response (already at one week) and a large reduction of PANSS total score (Strong response group). After one year, the reduction of PANSS total score was 58%. There was a difference in the starting point for PANSS total score in these two groups with a higher value at baseline in the Strong response group, but the ending point was quite similar. A third group of patients (N= 19, 13%) followed a trajectory of poor improvement and a 9% reduction in PANSS total score over the studied period (Slight response group). The demographic variables age, sex, civil status and living alone, or drug naivety did not predict participants grouping in the various trajectories. Furthermore, we examined the predictive value of different antipsychotic drug treatment for the different trajectories with the "Intention to treat" method. There was a statistically significant difference in favor of amisulpride treatment for belonging to the Strong response group, while olanzapine strongly predicted the belonging to the Slight response group. There was no significant difference among the antipsychotic drugs regarding the Good response group. Discussion: Most patients (74%) with a schizophrenia spectrum diagnosis showed a good response during the one year follow-up and another 13% showed a remarkable strong improvement. That means that a total of 87% of patients had a satisfactory course of illness during the first year. Use of amisulpride predicts a better course compared to aripiprazole and olanzapine. This finding can be useful for clinicians when selecting antipsychotic drugs for their patients.